Raising Economic Performance by Fostering Product Market Competition in Germany - Fuentes, Andrés (OECD Publishing, 2006)
Much scope remains to make regulation of product markets more conducive to competition ? notwithstanding progress in recent years ? with substantial benefits for consumer welfare, productivity and employment. While the general competition legislation and enforcement framework is mostly effective, measures need to be taken to reduce administrative burdens on entrepreneurship and reduce the involvement of the government in business sector activities, notably through accelerated privatisation. Policies favouring small enterprises need to be revised, with a view to fully exposing them to competition and avoiding disincentives for small firms to grow. Substantial regulatory challenges exist in specific sectors, notably in the energy and railway industries where non-discriminatory access of market entrants to networks needs to be improved. Environmental objectives in energy market regulation could be achieved at lower cost. In the telecommunications industry, competition in the local loop can be strengthened. Regulation of the liberal professions is among the most restrictive in the OECD. Entry barriers need to be eliminated in crafts. and restrictions on large-scale retailing development could be eased. This paper relates to the 2006 Economic Survey of Germany (www.oecd.org/eco/surveys/germany)
Keywords: Economics; Germany